Social security reforms and early retirement - Hans Fehr; Wenche I. Sterkeby; Øystein Thøgersen (University of Würzburg, Department of Economics, 2000)
In order to stimulate labor market participation and improve the financial viability of the social security systems, many recent reform proposals in various OECD economies suggest to scale down the non-actuarial parts of the pension systems. These reforms have a flavour of increased efficiency at the costs of welfare losses for low income individuals. Investigating such a belief, we employ an overlapping generations model which features an endogenous retirement age and heterogenous individuals within generations. Based on a simple theoretical version of the model we demonstrate that high income individuals are likely to gain. The sign of the welfare effect for low income households is ambiguous because we do not know whether the effect of lower pension benefits is offset by the effect of a reduced tax-burden. Employing an extended CGE version of the model, which is calibrated to the Norwegian economy, we consider five reform proposals. It turns out that the various reforms which scale down the public non-actuarial pension system, lead to increases in the retirement age and steady-state welfare gains for all income classes.
Keywords: H55; H23; E62; 330; Social security; tax-transfer policies; induced retirement; pensions